Contemporary and Universal Themes in the Plays of Mahesh Dattani: Exploring societal barriers and taboo topics in Mahesh Dattani's plays (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present paper intends to consider certain chose plays of Dattani to deliver the contemporary themes managed by him. During the time spent scrutinizing the mature age standards and shows of our general public he raises the issues like – homosexuality, lesbianism, youngster sexual maltreatment and strict bigotry that how profoundly our psyches have oppressive hindrance regardless of our liberal falsification.